Epidemiology of Salmonella enterica Serotype Dublin Infections among Humans, United States, 1968–2013 - R. Reid Harvey; Cindy R. Friedman; Stacy M. Crim; Michael Judd; Kelly A. Barrett; Beth Tolar; Jason P. Folster; Patricia M. Griffin; Allison C. Brown (Emerging Infectious Diseases, 2017)
Salmonella enterica serotype Dublin is a cattle-adapted bacterium that typically causes bloodstream infections in humans. To summarize demographic, clinical, and antimicrobial drug resistance characteristics of human infections with this organism in the United States, we analyzed data for 1968–2013 from 5 US surveillance systems. During this period, the incidence rate for infection with Salmonella Dublin increased more than that for infection with other Salmonella. Data from 1 system (FoodNet) showed that a higher percentage of persons with Salmonella Dublin infection were hospitalized and died during 2005−2013 (78% hospitalized, 4.2% died) than during 1996–2004 (68% hospitalized, 2.7% died). Susceptibility data showed that a higher percentage of isolates were resistant to >7 classes of antimicrobial drugs during 2005–2013 (50.8%) than during 1996–2004 (2.4%).